Sabine MacCormack and the Andes - MacCormack, Catherine (2019)
Sabine MacCormack was a voyager in many worlds and many cultures throughout a life that came to reflect a synthesis of realities into a whole greater than the sum of the parts. Out of pasts that signified loss and war she charted new territories of personal healing and interdisciplinary cultural understanding. Sabine’s extensive and direct experience in Andean landscapes came to guide her thinking, reflecting community, belonging and her spiritual presence in the physical world.